To resist or to purchase: The causal mechanism of binge-watching and program purchase. (September 2022) - Song, Lianlian; Zhang, Qiuxiang; Hu, Baixue; Mou, Jian
Abstract: Binge-watching via video websites has become a popular viewing behavior. Managers of such sites have attempted to launch related business strategies but have thus far failed. Theoretical guidance on the causal mechanisms that drive binge-watching behavior and effective business strategies is very limited. This study aims to fill this gap by constructing a psychological reaction model to explain how binge-watching behavior motivates consumers to purchase subsequent episodes of a program. We employ psychological reactance theory to model the psychological reaction process when binge-watching is stopped by a payment requirement. Based on a survey and two experimental studies, we confirm the causal relationship between binge-watching and program purchase, which provides an alternative understanding of binge-watching that conflicts with a previous finding whereby binge-watching behavior reduces paid subscriptions. We also confirm the significant difference in response to a payment requirement between binge- and non-binge-watching, and verify the boundary condition that distinguishes binge- and non-binge-watching behavior. Highlights: This study explains how binge-watching behavior motivate consumers to purchase subsequent episodes of a program. The psychological reactance theory has been employed to study binge-watching behavior. This study confirms the causal relationship between binge-watching and program purchase.